South Africa's chemical and biological warfare programme 1981-1995 - Gould, Chandré (Rhodes University, Faculty of Humanities, Department of History, 2006)
In 1981 the apartheid military initiated a chemical and biological warfare (CBW) programme (code-named Project Coast). The programme, terminated in 1993, was aimed at developing novel irritating and incapacitating agents for internal and external use, covert assassination weapons for use against apartheid opponents, and defensive equipment for use by South African Defence Force (SADF) troops in Angola. The CBW programme was driven by a single individual, Dr Wouter Basson, who reported to a military management committee (the Co-ordinating Management Committee) which comprised a select group of high ranking officers. Practical and financial oversight of the programme was weak which allowed both for the abuse of programme funds and for senior military officers to deny knowledge of aspects of the programme. The biological component of Project Coast was conducted in violation of the commitments of the South African government to the Biological and Toxins Weapons Convention (BTWC). While the state's commitment to the BTWC was one of the factors considered when initiating the programme, it was not a sufficient constraint to prevent the development of the biological weapons programme, but rather influenced its structure such that the programme could avoid national and international detection. Despite efforts to conceal the military front companies where the chemical and biological warfare (CBW) research and development was undertaken, evidence presented in this thesis shows that the United States had sufficient information about the programme to have been aware of its existence. Yet, it was only in 1993, on the eve of the democratic election in South Africa, that any attempt was made by the US administration to pressure the government to terminate the programme. This thesis considers the factors which influenced the decision to develop Project Coast; the structure and nature of the programme; the motivations of scientists to become involved in the programme and remain involved; the use of chemical and biological agents against opponents of the state, and the factors which influenced the termination of the programme on the eve of the first democratic elections in 1994. It also considers the nature and exent of international support, both tacit and overt, for the programme and argues that the failure of Western nations to call for the termination of the programme before the early 1990s was a function of political expediency and indicates a significant weakness in the ability of international agreements to constrain the development of such programmes.
Keywords: Basson, Wouter, 1950-; Basson, Wouter, 1950- -- Trials, litigation, etc.; Biological warfare -- South Africa; Chemical warfare -- South Africa; Trials (Political crimes and offenses) -- South Africa; South Africa -- Politics and government -- 20th century